TRPV6 deficiency attenuates stress and corticosterone-mediated exacerbation of alcohol-induced gut barrier dysfunction and systemic inflammation - Meena, Avtar S.; Shukla, Pradeep K.; Rao, Rupa; Canelas, Cherie; Pierre, Joseph F.; Rao, RadhaKrishna (Frontiers in Immunology, 2023)
Chronic stress is co-morbid with alcohol use disorder that feedback on one another, thus impeding recovery from both disorders. Stress and the stress hormone corticosterone aggravate alcohol-induced intestinal permeability and liver damage. However, the mechanisms involved in compounding tissue injury by stress/corticosterone and alcohol are poorly defined. Here we explored the involvement of the TRPV6 channel in stress (or corticosterone) and alcohol-induced intestinal epithelial permeability, microbiota dysbiosis, and systemic inflammation. Chronic alcohol feeding was performed on adult wild-type and TRPV6-/- mice with or without corticosterone treatment or chronic restraint stress (CRS). The barrier function was determined by evaluating inulin permeability in vivo and assessing tight junction (TJ) and adherens junction (AJ) integrity by immunofluorescence microscopy. The gut microbiota composition was evaluated by 16S rRNA sequencing and metagenomic analyses. Systemic responses were assessed by evaluating endotoxemia, systemic inflammation, and liver damage. Corticosterone and CRS disrupted TJ and AJ, increased intestinal mucosal permeability, and caused endotoxemia, systemic inflammation, and liver damage in wild-type but not TRPV6-/- mice. Corticosterone and CRS synergistically potentiated the alcohol-induced breakdown of intestinal epithelial junctions, mucosal barrier impairment, endotoxemia, systemic inflammation, and liver damage in wild-type but not TRPV6-/- mice. TRPV6 deficiency also blocked the effects of CRS and CRS-mediated potentiation of alcohol-induced dysbiosis of gut microbiota. These findings indicate an essential role of TRPV6 in stress, corticosterone, and alcohol-induced intestinal permeability, microbiota dysbiosis, endotoxemia, systemic inflammation, and liver injury. This study identifies TRPV6 as a potential therapeutic target for developing treatment strategies for stress and alcohol-associated comorbidity.